Postglacial Faults in Fennoscandia: Targets for scientific drilling - Kukkonen, Ilmo T.; Olesen, Odleiv; Ask, Maria V. S. (GFF, 2010)
During the last stages of the Weichselian glaciation (ca. 9,000-15,000 years B.P.), reduced ice loads and glacially affected stress fields resulted in active faulting in Fennoscandia with fault scarps up to 160 km long and up to 30m high. These postglacial (PG) faults are usually SE dipping, SW-NE oriented thrusts, and represent reactivated, pre-existing crustal discontinuities. Postglacial faulting indicates that the glacio-isostatic compensation is not only a gradual viscoelastic phenomenon, but also includes unexpected violent earthquakes, suggestively larger than other known earthquakes in stable continental regions. We explore here possibilities and benefits for investigating, via scientific drilling, the characteristics of postglacial faults in northern Fennoscandia, including their structure and rock properties, present and past seismic activity and state of stress, as well as hydrogeology and associated deep biosphere. The research is anticipated to advance science in neotectonics, hydrogeology and deep biosphere studies, and provide important information for nuclear waste disposal, petroleum exploration on the Norwegian continental shelf and studies of mineral resources in PG fault areas. Validerad; 2010; 20100511 (maas)